Catalytic hydrodeoxygenation of dibenzofuran to fuel graded molecule over mesoporous supported bimetallic catalysts - Ambursa, Murtala M.; Lee, Hwei Voon; Juan, Joon Ching; Yahaya, Yakubu; Appaturi, Jimmy Nelson (Elsevier, 2019)
The present study focuses on hydrocarbons production (bicyclohexane) from hydrodeoxygenation of dibenzofuran over Cu-Ni/Ti-MCM-41 catalysts at mild reaction conditions. The hydrodeoxygenation activity of Cu-Ni/Ti-MCM-41 catalysts was optimized via Ni loading at reaction conditions of 260 °C, 10 MPa and 6 h in batch reactor. Those loading arounds the optimum points (5–10 wt%) were characterized by TPO, RAMAN, XRD, TPR, FESEM and ICP-MS analysis. The catalytic reactions pathway for conversion of dibenzofuran to bicyclohexane were investigated using optimum catalysts (7.5 wt% Ni loading) and reaction mechanism was then proposed. The characterization results showed that Cu-Ni dispersion and catalysts reducibility decreased with continuous increment of Ni loading above 7.5 wt%. The structure activity correlation showed that the dispersion and reducibility enhanced conversions and hydrocarbons selectivity. The highest conversion of dibenzofuran (85.46%) and selectivity of bicyclohexane (58.77%) were found with 7.5% Ni loading. Further addition of Ni loading could lead to decreasing of both activity and selectivity due to poor dispersion and agglomeration as well as low reducibility as Ni loading crossed the optimum points. The product distribution study indicated that the presence of other by-product such as cyclohexyl-benzene, tetra-hydro-dibenzofuran, cyclohexyl-cyclohexanol, cyclohexyl-cyclohexanone, 1-cyclohexyl-cyclohexene, 2-cyclohexyl-phenol. The proposed reaction mechanisms showed that the conversion of dibenzofuran was initiated by partial hydrogenations followed by deoxygenations and subsequently dehydrated to bicyclohexane.